Potency of Pulai (Alstonia Scholaris) As an Immunostimulant - Antania Phelia Zen; Soilia Fertilita (Fakultas Kedokteran Universitas Sriwijaya, 2023)
South Sumatera is one of provinces in Indonesia with broad peat soil ecosystem. Pulai or Alstonia scholaris is an evergreen plant commonly grow in peat soil ecosystem dan can be found in numerous areas in South Sumatera. Pulai has been globally used as traditional medicine to treat various kinds of disease ranging from gastrointestinal disorder, skin diseases, to anti-cancer. Therefore, researchers have been intrigued to analyze pharmacological aspect of Pulai. Several prior studies have found a large number of compounds within Pulai and a handful of them have been proved to function as anti-oxidant, anti-inflammation, anti-malaria, and even as immunomodulator. The present article is aimed to give preferences around the potential of Pulai or Alstonia scholaris as immunostimulant.